2021
DOI: 10.1371/journal.pone.0249346
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical characteristics of Egyptian male patients with COVID‐19 acute respiratory distress syndrome

Abstract: Background Coronavirus disease 2019 (COVID-19) is a serious illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and in severe cases associated with acute respiratory distress syndrome (ARDS). Objective To describe the clinical characteristics of patients with ARDS-COVID-19. Materials and methods This study involved 197 male Egyptian participants, among them111 COVID-19 patients presented with ARDS, 60 COVID-19 patients presented with non-ARDS, and 26 Non-COVID-19 patients. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…We found that fever, fatigue, and cough were the predominant symptoms, while sore throat, loss of taste, anosmia, and GIT symptoms were reported but with less frequency. These observations are in line with the findings of previous investigations (Doghish et al, 2021;Ibrahim et al, 2021;Alotaibi et al, 2022b;Cascella et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found that fever, fatigue, and cough were the predominant symptoms, while sore throat, loss of taste, anosmia, and GIT symptoms were reported but with less frequency. These observations are in line with the findings of previous investigations (Doghish et al, 2021;Ibrahim et al, 2021;Alotaibi et al, 2022b;Cascella et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…The clade 20A with the S_D614G mutation was reported in 17 samples. Our findings regarding the prevalence of different clades during the third wave of the COVID-19 pandemic are consistent with previous studies conducted in Egypt and worldwide ( Davies et al, 2021 ; Doghish et al, 2021 ; Gravagnuolo et al, 2021 ; Alotaibi et al, 2022a ; Hart et al, 2022 ; Lambrou et al, 2022 ; Seadawy et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“… 9 This reduction has also been shown to be associated with poor outcomes. 10 , 11 In addition, hyperinflammation seems to contribute to COVID‐19‐related coagulopathy, and microthrombosis was reported to occur in almost every system, including the musculoskeletal system. 12 Not only lower lymphocyte levels but also elevated levels of d ‐dimer are related to poor outcomes 13 and this elevation may be related to this coagulopathy in those of our patients whose musculoskeletal symptoms began with or were aggravated by COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of CRP levels in association with COVID-19 in Africa appear to be rare, but the metabolic marker may not be rare. Some reports indicated that CRP levels were associated with adverse outcomes in patients [ 89 91 ]. In general, CRP levels are high in many African countries or in African Americans, especially in association with diabetes, hypertension, or infectious diseases [ 92 ].…”
Section: The African Continent and Sars-cov-2mentioning
confidence: 99%